Investigations on microstructure, thermo-mechanical and tribological behavior of graphene oxide reinforced AA7075 surface composites developed via friction stir processing. (24th March 2023) - Nathan, S. Ragu; Suganeswaran, K.; Kumar, Surya; Thangavel, P.; Gobinath, V.K.
Abstract: Surface composites (SCs) are fabricated through reduced graphene oxide (RGO) particulates by adopting friction stir process (FSP) route to enhance the mechanical and thermal properties suited for cylinder liner applications. Microstructural examination reveals that both dynamic recrystallization phenomenon and particle stimulated nucleation happens in the duration of processing phase and owes to a fine and homogenous distribution of reinforcements in the matrix surface. Moreover, no sort of noticeable defects are formed between the base matrix and SC layer with prominent interface. An indigenous experimental setup is fabricated for the measurement of thermal conductivity of SCs. Percolation effect of reduced graphene oxide (RGO) particulates enhance the thermal conductivity of single pass SC specimen (158.6 W/mK) as compared to base metal (146 W/mK). Formation of highly conductive RGO through reduction of oxygen level owing to the heat generation at the processing stage that favors for the high heat dissipation of the five pass specimen (201.5 W/mK). Decremented interparticle spacing of the aforementioned specimen through reduced grain size (9 μm) enhances the impact toughness. Increased number of dislocations through grain refinement in the five pass specimen relieves the internal stress at a more possible extent which significantly reduces the coefficient of thermal expansion (CTE) value to 7.18 × 10 −4  K −1 . Superior Vickers hardness value (2188 MPa) enhances the specimen wear resistance. The worn morphology divulges the mild adhesive with abrasive behavior. Highlights: Incorporation of graphene oxide particles in aluminium composite to use in cylinder liner and high temperature applications Graphene oxide is used as reinforcement for aluminium composite to enhance the mechanical properties and thermal conductivity Graphene oxide particles distributed homogenously and retained in elemental form without any interfacial reaction Graphene oxide particles enhance the toughness and wear resistance